Revealing the film "budi pekerti": Digital platform in anti-cyber bullying character education reform - Mujiwati, Yuniar; Daryono, Daryono; Syaifudin, Khamdan (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
Film has a unique ability to influence and stimulate minds, a fact that cannot be ignored in the digital age. This research explores the merging of technology and morality, creating a medium that impacts audience thoughts and feelings. The focus is on character-based learning strategies to instill positive values and ethics. Directed by Wregas Bhanuteja, the film "Budi Pekerti" narrates the main character's development, reflecting a journey to adulthood while emphasizing essential moral values."Budi Pekerti" pioneers a new dimension in character education, adapting to a world where technology is deeply embedded in daily life. The film invites viewers to explore the main character's story through various challenging situations in cyberspace. From social media interactions to moral conflicts online, the film highlights inclusive character learning, promoting values such as honesty, empathy, responsibility, and patience through conflict and character growth. The research uses Documentation Notes as its instrument. The results and discussion of the film's substance, semiotics, and anti-bullying values provide a deep understanding of the ethical implications of everyday actions online. This film is not only an entertainment medium but also a social movement encouraging audiences to combat cyberbullying and build strong characters resilient to negative online pressures.